Business analyst’s process in developing user interface in the banking sector : Case study - Hämäläinen, Meiju (My University, 2020)
Skilled and educated business analysts with knowledge from both sides business and information technology are in need. It is critical when designing a usable user interface in the banking sector to overcome the multipart structure and complexity. It is crucial to examine the problem areas and plan specific guidelines before starting the development process. This research is needed to understand what are the business analyst’s process phases when developing a new user interface in the banking sector. Furthermore, the business analyst’s roles in a company are under consideration. This study observes how the business analyst approaches and plans the development process. This Master’s thesis used a case company from the banking sector to conduct business analyst’s process in developing a user interface. Moreover, this study aims to identify are business analysts in the case company applying the same process phases than in the presented literature. This research was conducted by practising Research Methods for Business Students written by Saunders (2007). The primary data was collected from three business analyst who worked at the case company. The empirical material was collected through one round of semi-structured interviews. Interviews were conducted one-on-one and were arranged to be face to face meetings. The business analysts were invited for the interviews through emails and the interview questions were presented in advanced. The findings revealed that a business analyst’s responsibility area can be as wide as the company has decided. A business analyst can have multiple roles and stands between business and information technology. There were found six phases which are used by the business analysts when developing a new user interface. The business analysts’ working at the case company described how the development phases do not proceed in chronological order. The development work is a back and forth going project. The user goals must be clarified before any development actions. In the banking sector, the target is to make a simple and user-friendly user interface. The rapidly developed information technology does not influence the business analysts in the case company as they comply with company standards.
Keywords: banking sector; user interfaces; analysts; fi=Tietojärjestelmätiede|en=Information Systems|; fi=Tietojärjestelmätieteen maisteriohjelma|en=Master’s Programme in Information Systems|